آثار إخلال البنك بالالتزام بالسرية المصرفية - مصطفاوي, وئام; منصوري, شفيقة; منصوري, مروة (University of Eloued جامعة الوادي, 2023)
يعد موضوع السرية المصرفية مف الموضوعات اليامة والمتصمة بالنظ الاقتصادية الحديثة، ذلؾ لما تضطمع بو المصارؼ مف دور فعاؿ في الحياة الاجتماعية والاقتصادية باعتبارىا محو ا ر أساسيا يرتكز عميو الائتماف وتمويؿ المشروعات التجارية والخدمية المختمفة والتي تعود بالفائدة عمى المجتمع ككؿ، فالسرية المصرفية مف الموضوعات بالغة التعقيد إذ أنيا تثير العديد مف المشكلبت التي يتسع مداىا مف الناحيتيف القانونية والعممية . تتناوؿ ىذه الد ا رسة النظا القانوني لمسرية المصرفية في التشريع الج ا زئري، وسيعتمد في الأساس عمى أسموب تحميؿ النصوص التي عالجت السرية المصرفية عمى وفؽ القواعد العامة في التشريعات الج ا زئرية إذ لا يوجد قانوف خاص لمسرية المصرفية في الج ا زئر.The subject of banking secrecy is one of the important issues related to modern economic systems, because of the effective role that banks play in the social and economic life as a basic axis on which credit and financing of various commercial and service projects are based that benefit the society as a whole. It raises many problems that are wide in scope from both the legal and practical points of view. This study deals with the legal system of banking secrecy in the Algerian legislation, and it will depend mainly on the method of analyzing the texts that dealt with banking secrecy in accordance with the general rules in the Algerian legislation, as there is no special law for banking secrecy in Algeria.
مذكرة ماستر
Keywords: السرية المصرفية النظا القانونية المسؤولية; bank secrecy - legal system - responsibility